SHORELINE CHANGE STUDY AT MUARA GEMBONG IN 2011-2021 USING LANDSAT SATELLITE IMAGERY - Afiifah Meizwar, Dara
The coast is an interaction area between land and sea where there are natural processes that are vulnerable to changes. Human activity brings changes that could cause an increase (accretion) or decrease (abrasion) of land on the coast. This research aims to determine the analysis of shoreline change that occurs at Muara Gembong in 2011-2021 and consider other conditions such as tides, bathymetry, waves, sedimentation, and land cover. Using extracted coastline from Landsat satellite imagery with band ratio and composite RGB methods, shoreline changes were analyzed by Digital Shoreline Analysis using the statistical methods of Net Shoreline Movements (NSM), End Point Rate (EPR), and Linear Regression Rate (LRR) to identify abrasion and accretion. Muara Gembong area was divided into Zone A which is located in the southern part and Zone B located in the northern part directly exposed to the Java Sea. Shoreline change at Muara Gembong for 10 years showed a tendency to accrete as far as 6.81 m. Rate of shoreline change value 0.18 m/year with accretion rate 12.24 m/year and abrasion rate -7.68 m/year. Besides, the total area of abrasion in 10 years of all zones comes to 805,562.41 m2 and the total area of accretion is 881,897.24 m2. The direction of sediment transport in Zone A leads south or to the left facing offshore, while in Zone B heading east or right facing offshore is influenced by the greatest contribution of wave energy that propagates from the northwest. The cause of abrasion is indicated more due to anthropogenic factors, namely land use in the form of ponds, while accretion in Zone A is caused by natural factors of sediment from rivers. Changes in the coastline in the Gembong Estuary are strongly influenced by human activities in addition to the influence of surrounding oceanographic phenomena.